POTENSI DAN OPTIMALISASI PRODUKTIVITAS NIRA NIPAH (Nypa fruticans) DARI METODA PENYADAPAN TRADISONAL KE TEKNOLOGI NON KONVENSIONAL - Sopyan Hadi; Thamrin Thamrin; Setyo S. Moersidik; Syaiful Bahry (Environmental Research Center (PPLH) of Udayana University, 2014)
The utilization of non-timber forest products of mangrove palm (Nypa fruticans Wurmb) ofsap produced through the process of tapping, is still made by the traditional way with theamount of sap production is still small or limited for consumption purposes. Sap whichcontains sugar has a potency to be fermented into ethanol which is a source of greenenergy. The problem is the amount of available sap as raw material obtained by traditionaltapping is still limited, therefore, more efforts to increase productivity are needed. Thepurpose of this study was to explore several methods of tapping palm from traditional waytowards non-conventional technologies. This study used an experimental method examiningseveral factors including 1) Duration of pre-tap (10 days, 20 days, 30 days) 2). Pre-tappingstimulation (without and with stimulation) 3) Type of container (non-vacuum container(traditional), 1.5 L small vacuum container, 2L medium vacuum container and 20L largevacuum containers). 4) The level of luxuriance palm leaf midrib (not dense 0-2 midrib, lessdense 3-4 midrib and dense > 4 midrib). Observed variables are sap volumes include volumesof palm sap/stem, sugar, tapping duration/stem. The result obtained from tapping processon mangrove forest in Lubuk Muda Village, Siak Kecil District, Bengkalis Regency RiauProvince showed that optimal productivity were obtained on 1). Pre-tapping stimulationat 30 days. 2) Treatment with pre-tapping stimulation. 3) Harvesting on the medium vacuumcontainer and 4) found in dense leaf midrib.